Higher Education, Globalization and the Critical Emergence of Diversity - Hershock, Peter D. (Paideusis)

(untitled) (Canadian Philosophy of Education Society, 2010)
Complex, risk-generating and predicament-laden patterns of global interdependence pose significant imperatives for radically reframing the purposes and provision of higher education. Changes already ongoing in higher education reflect and respond to global dynamics that are intensifying interdependence and, at the same time, deepening inequalities both within and among societies. Recognizing this is to recognize the need to question whether the arcs of change in higher education should remain passively entrained with globalization-driven magnifications and multiplications of difference, or whether higher education can and should play a unique and critical role in reorienting the dynamics of global interdependence. This paper argues that if current trends toward both institutional and epistemic differentiation can be inflected toward enhancing diversification—rather than mere variation—21st-century higher education can come to serve as a global relational commons crucial to realizing ever more deeply shared and equitable expressions of global flourishing and public good.